2012
DOI: 10.1002/hlca.201100275
|View full text |Cite
|
Sign up to set email alerts
|

Two New Sesquiterpenes from the Marine Fungus Eutypella scoparia FS26 from the South China Sea

Abstract: A new monocyclofarnesane-type sesquiterpene, 3,7,10-trihydroxy-6,11-cyclofarnes-1-ene (1), and a new acorane-type sesquiterpene, 8-(hydroxymethyl)-1-(2-hydroxy-1-methylethyl)-4-methylspiro[4.5]-dec-8-en-7-ol (2), were isolated from the culture of Eutypella scoparia FS26 from the South China Sea, along with three known terpenes, 3 -5. The structures of these compounds were determined by extensive analysis of their spectroscopic data as well as by comparison with literature reports. The isolated compounds 1 -5 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The HMBCs from H-C (14) to C(7), C(8), C(9), and C(13), from H-C(15) to C(12), C(13), C (14), and C (17), from Me (20) to C(1), C(9), and C(10), from HO-C(9) to C(9) and C(10), and from HO-C(6) to C(5), C(6), and C (7) corroborated the skeleton of rings B and C with Me (20) at C(10) and two hydroxy groups at C(6) and C(9), respectively. Moreover, correlations from H-C (15) and H-C(16) to C(13), and from Me (17) to C(13), C (14), and C(15) indicated that Me (17) and CH(15)=CH 2 (16) were attached to C (13). Finally, the planar structure of compound 1 was confirmed as depicted.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The HMBCs from H-C (14) to C(7), C(8), C(9), and C(13), from H-C(15) to C(12), C(13), C (14), and C (17), from Me (20) to C(1), C(9), and C(10), from HO-C(9) to C(9) and C(10), and from HO-C(6) to C(5), C(6), and C (7) corroborated the skeleton of rings B and C with Me (20) at C(10) and two hydroxy groups at C(6) and C(9), respectively. Moreover, correlations from H-C (15) and H-C(16) to C(13), and from Me (17) to C(13), C (14), and C(15) indicated that Me (17) and CH(15)=CH 2 (16) were attached to C (13). Finally, the planar structure of compound 1 was confirmed as depicted.…”
Section: Resultsmentioning
confidence: 78%
“…Fungus of the genus Eutypella have been reported to be mainly distributed the South China Sea, tropical forests of Australia and Thailand, and the soil of Arctic and Antarctica . Secondary metabolites with extensive structural diversity from this genus, including sesquiterpenoids, pimarane diterpenoids, cytochalasin derivatives, γ ‐lactones, cyclic dipeptides, and cytosporin‐related compounds, showed various bioactivities, such as antimicrobial, antitumor, and immunosuppressive activities . Eutypella sp.…”
Section: Introductionmentioning
confidence: 99%
“…A new monocyclic farnesyl sesquiterpene named 3,7,10-trihydroxy-6,11-cyclofarnes-1-ene ( 61 ) together with a new acorane sesquiterpene, 8-(hydroxymethyl)-1-(2-hydroxy-1-methylethyl)-4-methylspiro[4.5]-dec-8-en-7-ol ( 62 ), were isolated from the marine-derived fungus Eutypella scoparia FS26 isolated from a sediment sample from the South China Sea ( Figure 4 ) [ 23 ]. Compounds 61 and 62 were investigated for cytotoxicity against a panel of cancer cell lines but they only showed a weak cytotoxic activity against MCF-7 cell line.…”
Section: Different Classes Of Terpenoidsmentioning
confidence: 99%
“…Chemical investigation of this fungus has resulted in the discovery of various types of metabolites, including chromenes (Pongcharoen et al, 2006;Sun et al, 2013), cytochalasins (Pongcharoen et al, 2006;Ciavatta et al, 2008;Sun et al, 2011aSun et al, , 2013, cytosporin-related compounds (Ciavatta et al, 2008), pimarane diterpenes (Pongcharoen et al, 2006;Sun et al, 2011bSun et al, , 2012a, sesquiterpenes (Sun et al, 2011a(Sun et al, , 2012b and steroids (Sun et al, 2011b). In this study, we chemically investigated secondary metabolites produced by E. scoparia PSU-H267 isolated from a leaf of Hevea brasiliensis collected in Songkhla Province, Thailand.…”
Section: Introductionmentioning
confidence: 97%